A Jordanian empirical study of the associations among transformational leadership, transactional leadership, knowledge sharing, job performance, and firm performance: A structural equation modelling approach. Issue 5 (13th June 2016) - Masa'deh, Ra'ed; Obeidat, Bader Yousef; Tarhini, Ali
Abstract : Purpose: – Knowledge sharing adoption has been considered as a significant practice for organizations. However, there is a modest empirical confirmation to indicate how these organizations value the richness of their knowledge capabilities. The purpose of this paper is to investigate both transformational and transactional leadership styles that influence employees' knowledge sharing practices, and the impact of the latter on job performance, and then on firm performance. Design/methodology/approach: – Data collected from 179 employees at the higher council of youth in Jordan were empirically tested using structural equation modelling. Findings: – The findings revealed that both transformational and transactional leadership styles have significant impact on job performance, and the latter on firm performance. Also, it was found that transactional leadership impacted knowledge sharing, whereas transformational leadership did not. Originality/value: – This research proposes a new approach to understand knowledge sharing adoption, and outlines some theoretical and managerial implications of the findings.